Au cœur de la vie familiale et sociale. Genre et petite enfance dans la famille royale carolingienne - Emmanuelle Santinelli-Foltz (Genre & Histoire)
Although the documentation makes little mention of children in general and even less of young children, it sometimes mentions their presence and their association with the uncertainties of the lives of their parents and of the group into which the conjugal unit fitted. This is especially the case for the Caroligian family, better informed by more diversified documents, at least for the generation of Charlemagne and the two generations that followed. The article focuses on identifying and crossing the data gleaned from the literature to capture, with a gendered approach, what early childhood might cover and what made its specificity. It will show that, from a very early age, children, girls and boys, were carefully cared for and, as full members of the family group, were associated with dynastic issues. Though difficult to pinpoint, the end of early childhood may have corresponded to the time when, around the age of 5-7, education became more clearly gendered.